2009
DOI: 10.1177/0091270009339189
|View full text |Cite
|
Sign up to set email alerts
|

Absence of QTc Prolongation in a Thorough QT Study With Subcutaneous Liraglutide, a Once‐Daily Human GLP‐1 Analog for Treatment of Type 2 Diabetes

Abstract: The objective of this study was to establish effects of liraglutide on the QTc interval. In this randomized, placebo-controlled, double-blind crossover study, 51 healthy participants were administered placebo, 0.6, 1.2, and 1.8 mg liraglutide once daily for 7 days each. Electrocardiograms were recorded periodically over 24 hours at the end of placebo and highest dosing periods. Four different models for QT correction were used: QTci, as the primary endpoint, and QTciL, QTcF, and QTcB as secondary endpoints. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 23 publications
5
42
0
Order By: Relevance
“…A randomized, placebo-controlled, cross-over study, found no clinically relevant prolongation in the QTc interval after daily doses up to 1.8 mg were given [20]. The maximum plasma concentrations (Cmax) in overweight and obese subjects treated with liraglutide 3 mg was similar to the Cmax observed in healthy volunteers.…”
Section: Pharmacologymentioning
confidence: 81%
“…A randomized, placebo-controlled, cross-over study, found no clinically relevant prolongation in the QTc interval after daily doses up to 1.8 mg were given [20]. The maximum plasma concentrations (Cmax) in overweight and obese subjects treated with liraglutide 3 mg was similar to the Cmax observed in healthy volunteers.…”
Section: Pharmacologymentioning
confidence: 81%
“…While liraglutide and other GLP-1 agonists have shown positive effects on haemoglobin A1c, body weight, and blood pressure in patients with type 2 diabetes, emerging data suggest potential cardioprotective effects and no clinically significant changes in repolarisation patterns, or effects on the QT interval. 15 It should be noted that the cardiovascular safety of liraglutide will be prospectively evaluated in the international LEADER™ trial, which is enrolling 9000 patients with type 2 diabetes and a broad range of cardiovascular risk, including known coronary heart disease. Patients will be randomised 1:1 to liraglutide or placebo and will be followed for up to 5 years for adjudicated macrovascular events including non-fatal MI, stroke, and cardiovascular death.…”
Section: Discussionmentioning
confidence: 99%
“…Exenatide, liraglutide, and albiglutide do not cause any clinically relevant increase in the QTc interval [98][99][100][101]. Exenatide does not prolong QTc even at supratherapeutic concentrations [102].…”
Section: Cardiovascular Systemmentioning
confidence: 99%